Weight Change in Patients with Type 2 Diabetes Starting Basal Insulin Therapy: Correlates and Impact on Outcomes. Issue 6 (October 2014) - Shaefer, Charles F.; Reid, Timothy S.; Dailey, George; Mabrey, Melanie E.; Vlajnic, Aleksandra; Stuhr, Andreas; Stewart, John; Zhou, Rong
Abstract: Background: An increase in body weight is a commonly perceived effect of insulin therapy for type 2 diabetes mellitus, and this may serve as a barrier to insulin initiation and usage.Objective: To investigate the baseline clinical and demographic factors associated with weight gain during insulin glargine therapy, and the implications of weight change on clinical outcomes.Methods: This was a retrospective analysis of patient-level data from phase 3 or 4 randomized controlled, treat-to-target (fasting plasma glucose [FPG] ≤ 100 mg/dL) trials evaluating basal insulin glargine for ≥ 24 weeks. The Pearson correlation coefficient and Cochran-Armitage trend statistic were used to calculate the existence of a trend between absolute and relative weight change, and relative glycated hemoglobin (HbA1c ) change from baseline; likelihood of achieving target HbA1c < 7.0%; change from baseline FPG; insulin dose requirements; incidence of hypoglycemia; and adverse events.Results: Eleven studies were included, encompassing a total of 2140 patients. Patients starting insulin glargine treatment gained a mean ± standard deviation 1.8 ± 3.7 kg (4.0 ± 8.2 lb). Most patients had limited weight change (± 2.5 kg or 5.5 lb). Younger age, higher baseline HbA1c, and higher baseline FPG were predictive of greater weight gain ( P < 0.0001). Those who gained more weight experienced the largest decrease from baseline in HbA1c and FPG. More weight gain was associated with higher insulin dose requirements, an increased risk of experiencing either symptomatic or glucose-confirmed (< 70 mg/dL) hypoglycemia, and more adverse events. Older patients (> 65 years) were less likely to gain weight or to experience glucose-confirmed hypoglycemia, but more likely to experience severe hypoglycemia.Conclusions: In this retrospective analysis of patient-level data, most patients had a stable weight (defined as ± 2.5 kg) after 24 weeks of insulin glargine, and weight gain varied with patient demographics. Therefore, insulin glargine can be used in these patient groups with type 2 diabetes without expectation of significant weight gain.